Seropositive Individuals: Socio-Behavioral Profile and Utilization of Integrated Counselling and Testing Centre Services - Naik , Poonam R; Nirgude , Abhay S; Nagaraj K; Vellanki , Venkata S; Prasad , V G; Takalkar , Anant (National Journal of Community Medicine, 2012)
Background and Objectives: The HIV pandemic has had a profound impact on the health and economic conditions of individuals. Integrated counseling and testing centre (ICTC) is the key to range of intervention in prevention and care for PLWHA. This study was undertaken to understand the epidemiological profile of HIV positive individuals and the ICTC linkages with other care and support services for PLWHA. Methods: A retrospective cross sectional study was undertaken in an Integrated Counseling and Testing Centre of a medical college in a rural area of Nalgonda district of Andhra Pradesh. Data was collected for all sero-positive individuals from ICTC registered during the period January 2011 to September 2011 period by using predesigned questionnaire. The number of individuals registered during this period was 123. Results: Mean age was 37.6 years (±12.48). Majority (43.44%) of them were illiterate. With reference to their occupational status 66.6 % of males and 62% of females were working on daily wages. Majority (93.33%) of the males and more than half i.e. 56.45% of the females were married. Statistically significant association was found between gender and educational status, occupational status and marital status. In reference to risk group 54.83% of females and 46.7% of males had multiple sexual partners, 23.33% of males were truckers. More than 90% of them were referred to ART center and RNTCP OPD. Conclusion: The study reflected the need to have specially packaged programmes on the risk and vulnerability to HIV/AIDS for specific groups like illiterates, poor occupational status. Consolidate and further strengthen the efforts done in developing linkages in care and support of PLWHA through ICTC.